2015
DOI: 10.1128/aem.00101-15
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic Conditions Promote Species-Specific Mutualism between Gut Microbes In Silico

Abstract: bThe human gut is inhabited by thousands of microbial species, most of which are still uncharacterized. Gut microbes have adapted to each other's presence as well as to the host and engage in complex cross feeding. Constraint-based modeling has been successfully applied to predicting microbe-microbe interactions, such as commensalism, mutualism, and competition. Here, we apply a constraint-based approach to model pairwise interactions between 11 representative gut microbes. Microbe-microbe interactions were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 61 publications
4
108
0
Order By: Relevance
“…5a). Consistent with one previous in silico study 33 , the presence of oxygen resulted in a decrease in commensalism and mutualism, especially for Gammaproteobacteria (Supplementary Fig. 6).…”
Section: Pairwise Interactions Of Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…5a). Consistent with one previous in silico study 33 , the presence of oxygen resulted in a decrease in commensalism and mutualism, especially for Gammaproteobacteria (Supplementary Fig. 6).…”
Section: Pairwise Interactions Of Modelssupporting
confidence: 91%
“…Pairwise simulations were performed on every possible pair of the 773 AGORA metabolic reconstructions (298,378 pairs). Microbial models were paired by introducing a common lumen compartment, as described elsewhere 33 , in which each model could secrete or from which it could take up metabolites. Dietary compounds were added to the lumen and byproducts were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Community models so far have been largely devoted to understanding general principles of community structure [24,83,[87][88][89], but also have accurately captured experimentally observed metabolic dependencies [7 , 18,89]. The next frontier for the models will be to provide hypotheses verifiable with the experimental approaches discussed above.…”
Section: In Silico Hypothesis Generationmentioning
confidence: 99%
“…For identifying potential exchanged metabolites, steady-state models are of particular interest as these can be applied with as little information as the identity of community members and their genome sequences [7 ]. These can be further extended, albeit for small communities and with additional information on the metabolic physiology of the community and its members, to address more complex problems such as community dynamics [86].Community models so far have been largely devoted to understanding general principles of community structure [24,83,[87][88][89], but also have accurately captured experimentally observed metabolic dependencies [7 ,18,89]. The next frontier for the models will be to provide hypotheses verifiable with the experimental approaches discussed above.…”
mentioning
confidence: 98%
“…This approach generated testable predictions about the metabolites exchanged between microbe and host, the ability of B. thetaiotaomicron to rescue certain lethal enzymopathies in the host, and the ability of the host to do the same for the bacterium. In a more complex study, the same research group modeled pairwise interactions between 11 representative gut microbes in conjunction with human small intestinal enterocytes, under three different diets [70]. They found that the anoxic conditions of the large intestine appear to drive mutualistic crossfeeding, resulting in a more complex ecosystem than is present in the less anoxic small intestine.…”
Section: Metabolic Models Of the Gut Microbiomementioning
confidence: 99%